Kahit konting pagtingin ([Manila] Viva Films, 1999)
She was his employer. He was her employee. But love knows no bounds, and soon, the master and the servant find themselves breaking rules and falling in love.
VCD
Fernando Poe, Jr., Sharon Cuneta
Keywords: Feature films